Analisis Penyerapan Tenaga Kerja Usaha Mikro Kecil Dan Menengah Kain Tenun Di Desa Kebon Ayu Kecamatan Gerung Kabupaten Lombok Barat: Analisis Penyerapan Tenaga Kerja Usaha Mikro Kecil Dan Menengah Kain Tenun Di Desa Kebon Ayu Kecamatan Gerung Kabupaten Lombok Barat - Siti Aliyah Lailatul Magfiroh; Nasruddin (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a key sector in regional economic development because they are able to absorb labor, increase community income, and preserve local wisdom. As a center for traditional woven fabric production, Kebon Ayu in Gerung, West Lombok, has both cultural and economic value. This village not only maintains cultural heritage but also provides employment opportunities for the community, especially for women. This study discusses the role of woven fabric MSMEs in labor absorption as an effort to improve the economic welfare of the community in Kebon Ayu. The objective of the study is to analyze the extent to which woven fabric MSMEs are able to absorb labor and the factors influencing it. This research employs a qualitative research method with data collection techniques through observation, interviews, and documentation. The data sources consist of primary and secondary data. The result of this study indicates that woven fabric MSMEs play a role in creating new employment opportunities, particularly for housewives. In addition, the existence of MSMEs can increase family income, expand community skills in the handicraft sector, and preserve local cultural traditions. However, there are several constraints, including limited capital, lack of design innovation, and limited market access. The suggestions are that the local government should provide support in the form of skills training, access to business capital, and strengthening marketing networks. Design creativity and product quality among MSME actors also need to be improved in order to compete in a broader market.